2022
DOI: 10.1088/1748-3190/ac8710
|View full text |Cite
|
Sign up to set email alerts
|

Get a grip: inward dactyl motions improve efficiency of sideways-walking gait for an amphibious crab-like robot

Abstract: Crabs are adept at traversing natural terrains that are challenging for mobile robots. Curved dactyls are a characteristic feature to engage terrain for resisting wave forces in surf zones. Inward gripping motions at the onset of stance could increase stability.Here, we add inward gripping motions to the foot trajectories of walking gaits to determine the energetic costs and speed for our 12 DOF crab-like robot, Sebastian. Specifically, we compared two gaits in which the step size (stance length) was the same,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The interaction between ULRs and the sediment is mediated by the feet, however, notwithstanding the great importance of this subsystem, little attention has been dedicated to this topic (figure 4(d)). Researchers from the Crab Lab of the Case Western Reserve University have recently focused on the use of tapered, curved feet (like crab dactyl shape) paired with a distributed inward gripping method, to allow the amphibious hexapod Sebastian (figure 3(B)) to anchor to the sediment and improve its speed and cost of transport on different kinds of sediment and in the presence of waves [66,92]. Similarly, even though never demonstrated on ULRs, the use of microspines [91], can yield excellent anchoring properties, especially on rocks.…”
Section: Interaction With the Sedimentmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between ULRs and the sediment is mediated by the feet, however, notwithstanding the great importance of this subsystem, little attention has been dedicated to this topic (figure 4(d)). Researchers from the Crab Lab of the Case Western Reserve University have recently focused on the use of tapered, curved feet (like crab dactyl shape) paired with a distributed inward gripping method, to allow the amphibious hexapod Sebastian (figure 3(B)) to anchor to the sediment and improve its speed and cost of transport on different kinds of sediment and in the presence of waves [66,92]. Similarly, even though never demonstrated on ULRs, the use of microspines [91], can yield excellent anchoring properties, especially on rocks.…”
Section: Interaction With the Sedimentmentioning
confidence: 99%
“…The category of ULRs is very heterogeneous in terms of morphology and size. Prototypes with one [70,71], two [75], four [68,72,89], six [24,84,102,103,107,108], and eight legs [87] were developed, and legs with one [99], two [71,92], three [24,72,109], or more [110] DoFs were employed. Naturally, ULRs with a higher number of DoFs are potentially more versatile and several behaviours can be implemented on the same robot.…”
Section: Modelling and Controlmentioning
confidence: 99%
“…A 7.4 V lithium polymer battery powers the motors. A basic gait is described in a companion paper [73] (figure B1 and table B1). We estimate the coefficient of friction between the substrate and the dactyls to be between 0.4 and 0.5 based on [74,75].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…In this paper, we propose the use of a legged crab-like robot with Hall effect-based sensors for UXO and non-UXO discrimination. In previous work, we have shown that hexapod robots with crab-inspired limbs are suitable for navigation in shallow, turbid water [ 11 ], making them suitable platforms for incorporating underwater UXO sensing strategies. We have also shown that Hall-effect magnetometers measuring the field of a magnet embedded in compliant robot limbs can be used to classify the terrain from measurements taken as the robot dynamically interacts with the terrain [ 12 ].…”
Section: Introductionmentioning
confidence: 99%